REPRODUKSI PAHAM KEAGAMAAN DAN RESPON TERHADAP TUDUHAN RADIKAL (Studi Kasus Pesantren Ngruki Pasca Bom Bali 2002) - Muhamad Murtadlo (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2017)
Pesantren Al Mukmin Ngruki Sukoharjo is often cited as an inspiration for radical Islam in Indonesia. This research examines the reproduction of religious understanding and the response to allegations of radicalism addressed to Pesantren Ngruki after the Bali bombings of 2002. This study includes qualitative research with case study approach. This study argues that a radical view of Islam can not be separated from social and historical context of this Islamic boarding institutions. Currently Pesantren Ngruki has undergone some changes in the orientation of education resulting from multiple causes, which are not limited by the case of Bali bombings only.